Responses of Sap Flow to Environmental Factors in Robinia pseudoacacia Plantations with Different Degrees of Degradation - MA Jun; HAN Lei; LIU Lili; WANG Nana; MA Yunlei; MA Shijie; WANG Yuan (Shuitu Baochi Xuebao)
［Objective］ Research on the characteristics of sap flow velocity and its responses to environmental factors in plantations with different degrees of degradation is helpful to reveal the mechanisms of forest degradation, and can provide a scientific basis for structure adjustment and management of regional plantations. ［Methods］ Taking Robinia pseudoacacia plantations in the east area of Yellow River in Ningxia as the research objects, the stem sap flow velocities of R. pseudoacacia with different degrees of degradation were measured by TDP thermal diffusion sap flow meter from May to October, 2023, and the environmental variables were monitored at the same time. The response relationships between environmental variables and the stem sap flow velocities of non-degraded R. pseudoacacia plantation (NDPP), moderately degraded R. pseudoacacia plantation (MDPP) and heavily degraded R. pseudoacacia plantation (HDPP) were studied. ［Results］ 1) The daily average sap flow velocity of NDPP, MDPP and HDPP were 2.32, 0.84 and 0.45 cm/h respectively. 2) With the aggravation of degradation, the response threshold of R. pseudoacacia sap flow velocity to atmospheric temperature (Ta) and saturated water pressure deficit (VPD) increased, while the response threshold to solar radiation (Sr) decreased. The critical response thresholds of sap flow velocity of R. pseudoacacia with different degradation degrees to environment variables were 29.6, 30.3 and 32.7 ℃ respectively in Ta, 1.14, 1.93 and 2.39 kPa respectively in VPD and 428, 314 and 222 W/m2 respectively in Sr. 3) The sap flow velocity of R. pseudoacacia decreased significantly with the decrease of soil water content, and the sensitivity of sap flow velocity to the change of soil water content decreased with the aggravation of degradation. 4) The contribution of environmental variables to sap flow velocity in stands with different degrees of degradation was different. With the aggravation of the degradation degree, the total effect of Sr, VPD and soil moisture on sap flow velocity decreased. ［Conclusion］ For degraded R. pseudoacacia forests, appropriate thinning could be used to reduce stand transpiration, improve rhizosphere soil moisture environment and increase the response sensitivity of trees to drought environment.